Multiple Disturbances of Existing Tunnels Caused by Deep Excavation and New Shield Tunnel - Haoran Li; Fei Ye; Enjie Su; Xingbo Han (Advances in Civil Engineering)
With the continuous development of urban underground spaces, new underground engineering approaches are becoming more similar to existing operating tunnels. Existing research is typically concerned with the impact of a single project, such as a new tunnel or deep excavation, on existing shield tunnels. There are few studies on the influence of both excavation and overcrossing tunneling on operational tunnels. Taking a section ranging from the Chengzhan Station to the Jiangcheng Road Station of Hangzhou Metro Line 7 as a case study, this study analyzes the automatic monitoring data of the existing tunnel within this section. Through data analysis, the influences of deep excavation and shield tunneling on the vertical settlement, horizontal displacement, segment convergence, and differential settlement of the tunnel ballast of the adjacent existing line segment are assessed. The influence of deep excavation and overcrossing tunneling on multiple disturbances of existing line tunnels is summarized. This study will be useful for similar projects involving deep excavation next to existing tunnels and overcrossing tunneling, as it will help clarify the protection range of existing lines and determine the displacement alarm value of existing structures.